Genome-scale metabolic modelling of Clostridium autoethanogenum - Norman, Rupert O.J. (2019)
Recent international directives promoting the reduced consumption of fossil fuels have warranted methods for effective carbon recycling. Subsequently, Clostridium autoethanogenum has attracted academic and industrial interest due to its ability to convert syngas components (CO, CO2 & H2) into valuable platform chemicals, including ethanol and 2,3-butanediol. Developing the metabolic conversions catalysed by C. autoethanogenum into an efficient bioprocess requires the accurate prediction of optimal metabolic steady states, which in turn necessitates the construction of a genome-scale model (GSM).